Predictive role of monocyte-to-lymphocyte ratio in patients with Klebsiella pneumonia infection: A single-center experience. Issue 38 (September 2019) - Wang, Jia-lu; Lu, Xiao-ye; Xu, Xin-hui; Zhang, Ke-ji; Gong, Hao; Lv, Dan; Ni, Zhu-ang; Zhu, Chang-qing
Abstract : Abstract: The aim of the study is to explore whether monocyte–to-lymphocyte ratio (MLR) provides predictive value of the severity in patients with Klebsiella pneumonia infection (KPI). Patients in a tertiary medical center with Klebsiella pneumonia infection from 2014 to 2017 were recruited in this study. Patients with Klebsiella pneumonia infection were stratified into two groups based on the National Early Warning Score (NEWS). MLR was calculated by dividing monocytes count by lymphocytes count obtained from routine blood examination. The area under the curve (AUC) values was determined using the receiver-operating characteristic (ROC) curve. The correlation between the variables was tested with Pearson or Spearman correlation analysis. Ordinal logistic regression analysis was used to assess the relationship between MLR and the severity of Klebsiella pneumonia infection. One hundred fifty-two patients were finally enrolled for analysis. Among those, 43 (28.29%) cases had severe KPI. MLR was found to be an independent risk factor of the serious Klebsiella pneumonia infection (OR: 23.74, 95% CI: 5.41–104.11, P < .001). Besides, MLR was positively correlated with NEWS score (r = 0.57, P < .001). In the receiver-operating characteristic (ROC) curve analysis, MLR, with an optimal cut-off value of 0.665, predicted the severe coronary lesion with a sensitivity of 79.4% and specificity of 84.4%. MLR was an independent predictor of the severe Klebsiella pneumonia infection. Compared with neutrophil-to-lymphocyte ratio (NLR), MLR has a better performance to evaluate the severity of Klebsiella pneumonia infection.